Constraints to implementing the food-energy-water nexus concept: Governance in the Lower Colorado River Basin. Issue 92 (February 2019) - Huckleberry, Justyn K.; Potts, Matthew D.
Highlights: A FEW nexus analysis in the Lower Colorado River Basin indicates that food production is not controlled by water availability. Rigid water law in the basin limits resource manager ability to respond to future economic or environmental stresses. Resource governance plays a strong formative role in the analysis and implementation of FEW nexus management strategies. Consistent watershed-level data would improve understanding of resource governance, management, and production dynamics. Abstract: The food-energy-water (FEW) nexus concept has emerged as a powerful approach to address the social and environmental challenges created by land and climate change. We present an analysis of the impact of the governance structure of the Lower Colorado River Basin (LCRB) on the implementation of the FEW nexus concept. Specifically, we quantified the linkages between food, energy, and water systems and then used two different future scenarios: (1) drought and (2) increased demand for alfalfa to look for the emergence of resource scarcity and/or vulnerabilities. Our results indicate that fluctuations in food production are not controlled by water availability but by the governance structure. Additionally, there is proportionally more water used for food than energy, and more energy used to move water to cities than water for agricultural production. Analysis of the production scenarios indicate tipping points of food, energy, and water resources based on climatic and consumptive trends that are not yet addressed by the rigid water laws in the LCRB. These results highlight the need for resource governance to play a strong formative role in the analysis and implementation of FEW nexus management strategies.